Peran Satuan Polisi Pamong Praja Dalam Penertiban Pedagang Kaki Lima Di Kota Semarang (Institut Pemerintahan Dalam Negeri, 2019)
Abstract Satuan Polisi Pamong Praja is in every Provincial Region and district and city that is tasked with enforcing the Regional Decree / Regulatory Regulations, organizing control and organizing community protection. Satuan Polisi Pamong Praja in Semarang is faced with various problems of order, especially Street Vendors (PKL). Semarang City as the Capital of Central Java Province, among others, is an area that is a life goal to change the economic situation of the community, among others, by selling as street vendors. With the increase in street vendors, the responsibility of Satuan Polisi Pamong Praja is increasingly heavy. How the role of the Satpol of Satuan Polisi Pamong Praja of the City of Semarang can control street vendors in an effort to uphold the order, cleanliness and beauty of the City through Regional Regulation No. 11 of 2000 concerning the Arrangement and Development of Street Vendors. Key words: Role, Satpol PP, order